Sustainable Urban Growth and Green Space Governance in Yogyakarta: Remote Sensing Insights and Lessons learned from Budapest (Integrating Remote Sensing into Urban Planning and Policy) - agustiyara, agustiyara; Mar Atun Saadah (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2025)
Rapid urbanization often leads to the loss of green spaces, posing challenges for sustainable and inclusive city planning. This study uses a remote sensing approach to map and analyze urban growth and green space dynamics in Yogyakarta, Indonesia, by combining Sentinel-1 and Sentinel-2 satellite data from 2015 and 2022. Supervised classification of land cover (built-up versus vegetated areas) was combined with the Normalized Difference Vegetation Index (NDVI) to quantify changes in green cover. The results for Yogyakarta reveal significant urban expansion, particularly towards the peripheral districts of Bantul and Sleman, accompanied by a decline in inner-city green spaces. In contrast, a parallel analysis of Budapest, Hungary, over the same period shows an overall increase in urban greenery and well-maintained green spaces within the city, reflecting effective urban planning interventions. These comparative findings suggest that urban growth in Yogyakarta has come at the cost of green space loss. In contrast, Budapest’s policies, including compact city strategies and green infrastructure development, have preserved and enhanced urban green spaces. Drawing on Budapest’s experience, this study discusses how Yogyakarta might adopt more inclusive and sustainable urban environmental governance. This study demonstrates the value of integrating multi-source satellite imagery for urban environmental monitoring. It provides policymakers with insight into how to balance urban growth with the conservation of green spaces.